Consumo, digestibilidade, desempenho e características da carcaça de ovinos alimentados com resíduo do maracujá (passiflora edulis l.) em substituição ao milho - Amorim, Raimundo Neilson de Lima (2015)
Two studies were conducted to evaluate effects of corn grain replacement with passion fruit by-product (PFB) in finishing lambs on feed intake, feedlot performance, carcass traits and digestibility. In study 1, 20 Morada Nova ram lambs (15,4±1,4kg BW) were used in a completely randomized design with 4 treatments: isonitrogenous (19% CP) experimental diets contained 30% Tifton-85 bermudagrass hay and 70% concentrate (soybean meal, wheat meal, corn and 0, 25, 50, or 75% PFB). Over a period of 21 d, lambs were housed in digestibility cages (14 d adaptation and 7 d data collection) and DM, CP and NDF digestibilities estimated by total fecal collection technique. In the study 2, 32 Morada Nova ram lambs (22.4 ± 3.2 kg BW) were housed in individual pens and assigned to a randomized block design (initial BW) and fed the same diets of study 1 for 78 d (14 d adaptation and 64 d data collection). DM and nutrient intakes, average daily gain (ADG) and gain to feed (G:F) were evaluated and after slaughter (32 kg), yields of hot carcass (HCY) and cold carcass (CCY) were calculated. Data from study 1 were analyzed using the procedure of SISVAR and means were compared with Tukey test (P < 0.05). For the study 2, data were analyzed with MIXED procedure with each animal as the experimental unit, and model effects included block and treatment. DM and CP digestibilities were not affected by PFB when it was added up to 50% (74.98 ± 2.0 and 77.38 ± 2.8%, respectively; P > 0.05). However, DM and CP digestibilities decreased in 75% PFB diet (69.7 ± 0.7 and 72.5 ± 1.1%, respectively). NDF digestibility was unaffected by treatments (P > 0.05), averaging 49.4 ± 3.4%. There were no differences in DM and digestible nutrient intakes (P > 0.05). No differences were evidenced (P > 0.05) in ADG (152 ± 0.03 g), G:F (0.147 ± 0.01 kg), HCY (46.6 ± 1.0%) and CCY (45.0 ± 1.0%). The data indicate that although passion fruit by-product decreases diets DM and CP digestibility, it is a suitable replacement for corn grain in diets for feedlot lambs when used at up to 75%